Study of Variation of Binder Materials On Permeability Of Foundry Green Sand - Widya Emilia Primaningtyas; Farizi Rachman; Tisya P. Ramadhani; Aminatus Sa'diyah (International Journal of Marine Engineering Innovation and Research, 2023)
The preparation of standards and procedures for the production process in the manufacturing industry plays an important role in achieving acceptable products and in accordance with the desired quality. Based on the data from the quality control report of a foundry company, casting defects slightly exceed the maximum reject rate. It was found that the moisture content in the molding sand produced according to the procedure exceeded the maximum water content in the molding sand. The research was conducted as an effort to improve the quality of the company's production in reducing reject products. Permeability values of molding sand and quantitative area of cast defects will be compared, as a variations of bentonite and molasses binders , in three variations of the percentage addition of binder, respectively: 1, 3, and 5%. The Anova Two Way approach was used to statistically assess the results of the permeability test of the test specimens to ensure the effect of the predictor variables on the response. The results indicated that the more molasses, 5% added to the molding sand, gave the highest permeability of 53.50 ± 0.50 cm3/minute and gave the lowest cast defect area of 11.97%. The addition of bentonite binder produces a phenomenon that is inversely proportional to the addition of molasses binder.